Pengaruh Labelisasi Halal dan Promosi terhadap Keputusan Pembelian di Store Beringin Rajawali Kota Palembang - Amir Salim; Rizki Novensi Yusta; Anggun Purnamasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
On an international scale, Indonesia is known as the initiator of the formation of the World Halal Council. Indonesia has the MUI (Indonesian Ulema Council), many decisions and decisions of the majority of Muslims in Indonesia are dependent on the MUI fatwa. In addition, Indonesia is the country with the largest Muslim population as a majority more than 87 percent of its population of 258 million identify themselves as Muslim. Analyzing the facts above, because the majority of Indonesian people are Muslims, then the Muslim community should make more purchases of products, especially food products, considering that humans need to eat. This study will explain the effect of halal labeling on purchasing decisions for pempek products at the Rajawali Beringin Store in Palembang City. In addition to halal labeling, other things that influence purchasing decisions. The most common thing is that many sellers use promotions to increase sales. There are many ways that are often used to attract consumers' purchasing power, such as discounts, buy 1 get 1 free, cashback, vouchers, promo codes, flash sales and many more. This study will also explain the effect of promotion on purchasing decisions for pempek products at the Rajawali Beringin Store in Palembang City. This study will explain the effect of halal labeling and promotion on purchasing decisions for pempek products at the Rajawali Beringin Store in Palembang City partially and simultaneously.